The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3cp01011b
|View full text |Cite
|
Sign up to set email alerts
|

Interface prompted highly efficient hydrogen evolution of MoS2/CoS2heterostructures in a wide pH range

Abstract: Interfacial electronic characteristics is crucial for hydrogen evolution reaction (HER), especially in nanoscale heterogeneous catalysts. In this work, we found that the synergistic promotions between CoS2 and MoS2 (2H-MoS2 and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…The HER mechanism in an alkaline medium involves three steps: 31,32 Volmer step: H 2 O + e − + H* → OH − Heyrovsky step: H* + H 2 O + e − → OH − + H 2 Tafel step : H* + H* → H 2 It is well known that the Volmer step is the adsorption reaction ( b = 120 mV dec −1 ), while the Heyrovsky ( b = 40 mV dec −1 ) and Tafel step ( b = 30 mV dec −1 ) are the electrochemical sorption and desorption of H 2 . 33 The Tafel slope of 80.6 mV dec −1 for FMS 0.5 illustrates that the HER reaction is in accordance with the Heyrovsky–Volmer mechanism. The interfacial coupling between the 1T-MoS 2 nanoflowers and FeS nanosheets in FMS 0.5 would promote the adsorption of H* and dissociation of H 2 O.…”
Section: Resultsmentioning
confidence: 63%
“…The HER mechanism in an alkaline medium involves three steps: 31,32 Volmer step: H 2 O + e − + H* → OH − Heyrovsky step: H* + H 2 O + e − → OH − + H 2 Tafel step : H* + H* → H 2 It is well known that the Volmer step is the adsorption reaction ( b = 120 mV dec −1 ), while the Heyrovsky ( b = 40 mV dec −1 ) and Tafel step ( b = 30 mV dec −1 ) are the electrochemical sorption and desorption of H 2 . 33 The Tafel slope of 80.6 mV dec −1 for FMS 0.5 illustrates that the HER reaction is in accordance with the Heyrovsky–Volmer mechanism. The interfacial coupling between the 1T-MoS 2 nanoflowers and FeS nanosheets in FMS 0.5 would promote the adsorption of H* and dissociation of H 2 O.…”
Section: Resultsmentioning
confidence: 63%
“…ΔG H is widely used as a measure of HER activity, with values close to zero indicating high catalytic activity. 68 Figure 7a shows the calculated adsorption energies of N,P-2H-MoS reduces ΔG H to 0.66 and 0.37 eV for N and P doping, respectively, which increases the number of active sites on the basal plane. For N,P-2H-MoS 2 , the ΔG H is comparable to that of N-MoS 2 (0.66 eV), while N,P-1T-MoS 2 exhibits a significantly lower ΔG H of 0.13 eV, indicating that the presence of the 1T phase activates more active sites and has a significant impact on the HER catalytic performance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…First, to validate the role of N and P doping, we calculated the adsorption energies (Δ G H ) of H* at different adsorption sites. Δ G H is widely used as a measure of HER activity, with values close to zero indicating high catalytic activity Figure a shows the calculated adsorption energies of N,P-2H-MoS 2 , N,P-1T-MoS 2 , N-MoS 2 , P-MoS 2 , 2H-MoS 2 and 1T-MoS 2 at S sites.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the implementation of heterogeneous structures offers a viable approach to improve the efficiency of electrocatalytic hydrogen evolution. By comprehensively considering factors such as material composition, vacancy, structure, and electron transfer, catalysts can be engineered to exhibit more efficient, stable, and controllable performance in reactions like water electrolysis. This is particularly significant for advancing the field of renewable energy, especially in the hydrogen industry. , Considering the properties of MoS 2 and CoS 2 , combining CoS 2 with MoS 2 , especially in the construction of effective heterojunctions, emerges as a highly potential approach for generating hydrogen across a wide range of pH levels. ,, Recent studies have provided valuable insights. Tao and co-workers demonstrated that both the two hexagonal (2H) and one trigonal (1T) phases of MoS 2 and CoS 2 heterojunctions exhibit synergistic catalytic activity surpassing that of individual components across the entire pH range .…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly significant for advancing the field of renewable energy, especially in the hydrogen industry. , Considering the properties of MoS 2 and CoS 2 , combining CoS 2 with MoS 2 , especially in the construction of effective heterojunctions, emerges as a highly potential approach for generating hydrogen across a wide range of pH levels. ,, Recent studies have provided valuable insights. Tao and co-workers demonstrated that both the two hexagonal (2H) and one trigonal (1T) phases of MoS 2 and CoS 2 heterojunctions exhibit synergistic catalytic activity surpassing that of individual components across the entire pH range . Wang and co-workers reported that 2D–2D CoS 2 –MoS 2 heterostructures, leveraging the synergistic effects of electron transfer and geometric structure, attain a current density of 10 mA cm –2 with overpotentials of 251 mV in alkaline and 218 mV in acidic conditions, respectively .…”
Section: Introductionmentioning
confidence: 99%